Thermal and structural alternations in CuAlMnNi shape memory alloy by the effect of different pressure applications - Canbay, Canan Aksu; Polat, Tercan (Elsevier Science Bv, 2017)
In this work the effects of the applied pressure on the characteristic transformation temperatures, the high temperature order-disorder phase transitions, the variation in diffraction peaks and the surface morphology of the CuAlMnNi shape memory alloy was investigated. The evolution of the transformation temperatures was studied by differential scanning calorimetry (DSC) with different heating and cooling rates. The differential thermal analysis measurements were performed to obtain the ordered-disordered phase transformations from room temperature to 900 degrees C. The characteristic transformation temperatures and the thermodynamic parameters were highly sensitive to variations in the applied pressure and also the applied pressure affected the thermodynamic parameters. The activation energy of the sample according to applied pressure values calculated by Kissinger method. The structural changes of the samples were studied by X-ray diffraction ( XRD) measurements and by optical microscope observations at room temperature.
Keywords: Cu-based shape memory alloys; Martensitic transformation; Shape memory effect; Pressure